PENDEKATAN PEMBELAJARAN BERBASIS NILAI DAN KARAKTER DI SD DALAM MENUMBUHKAN PROFIL PELAJAR PANCASILA - Dina Lastria (CV. ADIBA AISHA AMIRA, 2026)
The value- and character-based learning approach in elementary schools is an educational strategy that emphasizes the integration of moral, social, and spiritual values into the entire learning process. This approach aims to develop students who are not only academically competent but also possess strong character aligned with the dimensions of the Profil Pelajar Pancasila, namely faith and devotion to God, noble character, global diversity awareness, collaboration, independence, critical thinking, and creativity. Through habituation, role modeling, value integration across subjects, and co-curricular as well as extracurricular activities, students are guided to internalize Pancasila values in their daily lives. Teachers act as facilitators and role models in creating a reflective, collaborative, and student-centered learning environment. Therefore, this approach significantly contributes to shaping a generation with integrity, strong character, and the ability to face global challenges while maintaining national identity.